2014
DOI: 10.3892/etm.2014.1884
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mild hypothermia therapy for neonatal hypoxic-ischaemic encephalopathy on brain energy metabolism using 18F-fluorodeoxyglucose positron emission computed tomography

Abstract: It remains unclear whether mild hypothermia affects energy metabolism in the brain tissue of newborns with hypoxic-ischaemic encephalopathy (HIE). The current study aimed to investigate the effect of mild hypothermia on energy metabolism in neonatal HIE and assess brain energy metabolism using position emission tomography/computed tomography (PET/CT) scanning. The mean standardised uptake values of 18F-fluorodeoxyglucose (18F-FDG) were used to determine the glucose metabolic rate in various brain anatomical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…As an isomer of glucose, it is usually absorbed and transported into the brain. 28 In F344 rat prolactinoma models, there is more uptake of 18 F-FDG in prolactinoma compared to the normal pituitary; it was consistent with the VEGF immunohistochemistry staining results. In the clinical applications, 18 F-FDG was used to detect tumors in the whole human body.…”
Section: Discussionsupporting
confidence: 81%
“…As an isomer of glucose, it is usually absorbed and transported into the brain. 28 In F344 rat prolactinoma models, there is more uptake of 18 F-FDG in prolactinoma compared to the normal pituitary; it was consistent with the VEGF immunohistochemistry staining results. In the clinical applications, 18 F-FDG was used to detect tumors in the whole human body.…”
Section: Discussionsupporting
confidence: 81%
“…Dropping temperatures to 20°C leads to cerebral metabolic rate of one fifth of that at normothermic values ( 29 31 ). As a consequence, the release of excitatory neurotransmitters is slowed and the function of ion pumps in the neuron membrane is altered, which are proposed to contribute to seizure suppression ( 30 32 ). However, the molecular basis underlying how hypothermia alleviates seizures has rarely been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…17 Recently, it was reported that treatment with mild hypothermia in newborns with hypoxic-ischemic encephalopathy was associated with an improvement (increase) in brain glucose utilization compared to babies undergoing standard supportive treatment. 18…”
Section: Pet Scans Of Baby Brainsmentioning
confidence: 99%